Kondisi Sosial Kehidupan Pemulung di Kota Makassar - Ardi M. Yusuf (Indonesian Journal Of Law Studies, 2023)
this studi aims to determine the socio economic conditions between scavengers  who  operate  in  the  landfill,  which  shows  that  the  social  and economic life of the scavenger community is still vulnerable to poverty, while the results of scavengers in the TPA have not been able to neutralize the needs of life. From the sale of used goods, carboard aqua bottles and so on. Socially people who work scavengers are people who come from groups who are very have to be at the disposal site every day. To collect every day used goods that they can use as rupiah to make a living.